Resiliencia y factores sociodemográficos involucrados en la presencia de sintomatología depresiva, ansiosa y de estrés en población adulta chilena durante la pandemia de COVID-19: Resilience and sociodemographic factors involved in the presence of depressive, anxiety and of stress symptoms in the Chilean adult population during the COVID-19 pandemic - Riquelme Lobos, Patricio Alejandro; Raipán Gómez, Paola Mabel Alejandra (Revista de Psicopatología y Psicología Clínica, 2021)
Resilience and sociodemographic factors involved in the presence of depressive, anxiety and of stress symptoms in the Chilean adult population during the COVID-19 pandemic Abstract: The COVID-19 pandemic has caused a great impact on people’s mental health. The objective of this study was to examine the role of resilience and sociodemographic factors involved in the presence of depressive, anxiety and stress symptoms in the Chilean adult population during the COVID-19 pandemic. A sample of 501 participants answered the Depression, Anxiety and Stress Scales (DASS-21) and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). The results indicate that there are high prevalence rates of mental health symptoms during the current health crisis. We found that resilience is inversely associated with the three types of symptoms, also turning out to be a predictor variable for them. It may be concluded that there are groups with a higher risk for experiencing higher levels of depressive, anxiety and stress symptomatology, which indicates the importance of developing strategies that promote mental health. Keywords: COVID-19; resilience; depression; anxiety; stress. Resumen: La pandemia COVID-19 ha provocado un gran impacto en la salud mental de las personas. El objetivo del estudio fue examinar el rol de la resiliencia y de factores sociodemográficos involucrados en la presencia de sintomatología depresiva, ansiosa y de estrés en población adulta chilena durante la pandemia por COVID-19. Una muestra de 501 participantes respondió las Escalas de Depresión, Ansiedad y Estrés (DASS-21) y la Escala de Resiliencia de Connor-Davidson de 10 ítems (CD-RISC-10). Los resultados indican que existen altas tasas de prevalencia de sintomatología de salud mental durante la actual crisis sanitaria. Encontramos que la resiliencia se asocia de forma inversa a los tres tipos de sintomatología, resultando ser, además, una variable predictora para estos. Se concluye que existen grupos con mayor riesgo de experimentar niveles más altos de sintomatología depresiva, ansiosa y de estrés, lo que indica la importancia de desarrollar estrategias que promuevan la salud mental. Palabras clave: COVID-19; resiliencia; depresión; ansiedad; estrés.